BAHASA DAN KECERDASAN ANAK - ., Ratna Wahyu Pusari . (MALIH PEDDAS, 2011)
BAHASA DAN KECERDASAN ANAK Abstract Â Language is a communication tool to convey ones intent or purpose. In this paper, language development is very important to support other developments. Today, childrenâs language development has less serious attention. Because most people assume if children can not speak is a natural thing. But communication between the child can be well maintained with the language so the child can build a relationship, and it is not surprising that the language is considered as one indicator of success of a child. Children that has a lot of talking, sometimes reflected of an intelligent child. This intelligence is an ability to use words effectively, whether oral or written. In other words, covered all the way to communicate, where thoughts and feelings expressed in the form of a symbol or symbols to express a sense, such as using oral, written, sign numbers, painting, and the mimic face.